Correlation of 2D:4D digit ratio and craniofacial shape in prepubertal children. - Valla, Kalliopy; Halazonetis, Demetrios J (Am J Hum Biol, 2014)
OBJECTIVES: The 2D:4D ratio is sexually dimorphic and is considered a proxy of prenatal androgen levels, or, according to recent evidence, is related to genes involved in ocular and palate development. Our aim was to investigate correlation between the 2D:4D ratio and the shape of the craniofacial skeleton in a population of prepubertal children. METHODS: We conducted a cross-sectional study in a group of 58 male and 59 female prepubertal children aged 7-12 years. Craniofacial shape was evaluated using 15 skeletal landmarks on lateral cephalometric radiographs and fingers were measured with a computer-assisted procedure that involved tracing the finger outline. Geometric morphometric analysis was applied to the craniofacial landmarks and multivariate regression between digit ratios and craniofacial shape was computed in shape space and form space. RESULTS: The male 2D:4D ratio was smaller than the female ratio (Cohen's d: 0.275 left hand, 0.126 right hand), but the difference was not statistically significant. Craniofacial shape did not show sexual dimorphism, but males were larger than females. No correlation was found between digit ratio and craniofacial shape in prepubertal children, either for the whole sample or for any of the two sex groups. CONCLUSIONS: As several factors might be involved in the development and growth of both the craniofacial complex and fingers, the 2D:4D ratio, a putative proxy for fetal sex-hormone levels, is probably unable to impose a measurable effect within the variation of a normal population. Future research needs to examine an adult sample for potential covariation arising after the pubertal growth spurt.
Keywords: Cephalometry; Child; Cross-Sectional Studies; Female; Fingers; Greece; Humans; Male; Maxillofacial Development; Skull